Past lives, present learners: Future directions for history education in virtual reality - Miriam Mulders; Kristian H. Träg; Lilly Kaninski; Lara Rahner (Computers & Education: X Reality)
This study investigates the relationship between presence and learning outcomes in Virtual Reality (VR) environments, with a focus on both cognitive and affective learning. Using the Anne Frank VR House, a virtual replica of a hiding place for a group of Jewish people during World War II, 74 university students explored how the feeling of presence affects knowledge acquisition and perspective-taking. The results showed a significant positive correlation between presence and perspective-taking, but no effect on knowledge acquisition, meaning that a higher sense of presence predicted higher perspective-taking, while knowledge scores did not. These findings highlight VR's potential to create a sense of presence and thus foster emotional engagement in history education, suggesting that empathy-driven learning may be an effective way to engage students with complex socio-political issues beyond factual knowledge.